PERANCANGAN SISTEM KENDALI OTOMATIK PROSES PENGOLAHAN LIMBAH CAIR TAHU BERBASIS MIKROKONTROLER AT89S52 - Barita Bram Ardiwinata Putra (SISFOTENIKA, 2011)
Abstract : Tofu industry is one of the people industries which are many in Pontianak. The existence of this industry causes a negative impact which is environmental pollution caused by tofu liquid waste. Tofu liquid waste is a kind of wastewater which is produced along with the making of tofu. The environmental pollution caused by tofu liquid waste can be overcome by giving the tofu liquid waste a treatment process before it’s being wasted to the environment. To make the treatment process easy, I desinged an automation control system for the tofu liquid waste treatment process. The controller is a microcontroller AT89S52 which is a cheap microcontroller and also easy-to-program. The assembly programming is used to program the microcontroller. The results showed 83,98 % of average reduction of Chemical Oxygen Demand (COD) for treatment process in 3 days. Keywords: tofu liquid waste, microcontroller AT89S52.